Social media promotion effect on product purchase decisions through word of mouth marketing - Wursan, Wursan; Rinandiyana, Lucky Radi; Badriatin, Tine (Linguistics and Culture Review, 2021)
This study aims to describe: (1). Promotion uses social media to influence purchasing decisions (2). Promotion with social media so that it can influence the word of mouth market (3) Promotion of word of mouth market in influencing product purchases (4) Promotion using social media word of mouth market in influencing product purchases. The method uses Quantitave, data collection techniques with questionnaires, samples with purposive sampling with a total of 150. Conclusions: (1) Social media promotion has an effect on product purchases with t-count = 8,664 value 0.000 < 0.05, coefficient value = 0.792, (2) Social media promotion affects word of mouth with, t-count = 4.395 with value = 0.000 <0.05, coefficient value = r 0.395, (3). Word of mouth market has an influence on product purchases, with t-count = 4.821 with a value = 0.000 <0.05, coefficient = 0.440 (4). Social media promotion affects purchasing decisions, with a coefficient = 0.0906 value = 0.0217 <0.05.